Call to expand teaching opportunities in rural family medicine. Issue 2 (22nd January 2020) - Walters, Lucie; Worley, Paul
Abstract : To build and sustain rural medical workforces internationally, the authors of this commentary argue for innovative small group pedagogy tailored to remote and rural family medicine.